Ảnh hưởng của lực ion và một số ion lạ đến động học phản ứng quang oxi hóa khử giữa phức rutheni(II) polypyridin và axtt amin tyrosin - Thủy, Phạm Thị; Ánh Hường, Nguyễn Thị; Ngọc Mai, Phạm Thị; Trường, Nguyễn Xuân (Vietnam Journal of Chemistry, 2017)
Ruthenium(II) polypyridine – [Ru(bpy)3]Cl2 complex give a maximum emission at lem = 605 nm and its excited state decays by the first-order equation with k0 = 1.64 (± 0.01) ´ 106 s-1. Kinetics of the photoinduced electron transfer reaction between [Ru(bpy)3]Cl2 complex and acid amine Tyrosine is investigated by time-resolved molecular emission spectroscopy. The results show that the photoinduced electron transfer rate constants (kq) vary small ( 7 %) in the solutions with ionic strength I = 0-0.05 M. However, kq-values decrease more than twice if I ³ 0.1 M. On the other hand, the presence of the specific ions such as Ca2+, NH4+ and PO43- in the solution does not influence the reaction kinetics. Keywords. Ruthenium(II) polypyridine, Tyrosine, ionic strength, photoinduced electron transfer, time-resolved molecular emission spectroscopy.